PERSPEKTIF PUBLIK TERHADAP TAGAR #kaburajadulu: SEBUAH ANALISIS SENTIMEN KOMUNIKASI DIGITAL DI INDONESIA: Sebuah Analisis Sentimen Komunikasi Digital di Indonesia - Manurung, Nida Azizah; Suparman (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This research analyzes public perspectives on the hashtag #KaburAjaDulu on social media X (Twitter) thatwent viral in Indonesia in early 2024. This hashtag reflects the young generation's disappointment with thesocio-economic conditions in the country. The research objective is to analyze public sentiment towards thehashtag using a quantitative approach. The method used was sentiment analysis with the VADER algorithm on413 relevant tweets during February 2025. The results showed that the majority of tweets (52.1%) had apositive sentiment, followed by negative (28.6%) and neutral (19.4%). Positive tweets generally expressedhope for a better life abroad, while negative tweets criticized domestic conditions. This research contributes tothe study of digital communication and public opinion, and can help policymakers understand the aspirations ofthe younger generation through their digital expressions.Keywords: #KaburAjaDulu, sentiment analysis, digital communication, public opinion, VADER.